Second Thoughts on Naturalistic Theism and Model of Levels of Analysis: A Response to Mark Harris - Bylica, Piotr (Filozoficzne Aspekty Genezy, 2021)
I shall show that Dr. Harris’ study of biblical scholarship is treated in a very serious manner in my paper, as it is the element identifying him as a representative of naturalistic theism (NT). NT is a position that has been recognized in the literature on science and religion for several years. Dr. Harris’ commitment to the rule of methodological naturalism in the natural sciences, as well as his lack of evidence for the limits of using it in his hermeneutical analysis of divine action, makes his academic papers represent the main assumptions of NT. Model of levels of analysis (MLA) helps to show the empirical character of accounts of divine action as an important part of the traditional theistic interpretation of this action, and scepticism towards such an interpretation as a main characteristic of all advocates of NT.